Application of the Min-Max Stock Method in the Inventory Control of the Raw Materials for the Cement Production at PT XYZ - Hasan, Iqbal Abdurrahman; Pulansari, Farida (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
PT XYZ is the largest cement manufacturer in Indonesia that produces cement with different types of cement, namely OPC, PCC, and PPC. The implementation of its production process, starts with the mixing of raw materials, processing, and packaging to the finished product, namely cement. PT XYZ has a problem in the form of raw material inventory that has not been well controlled because the raw materials are often placed outside the storage area provided by the company due to overloading, thus taking up space that should not be used as a raw material storage area. In this study, the minimum-maximum method is applied to 4 types of raw materials, silica sand, gypsum, trass, and fly ash. By determining the amount of safety stock, minimum stock, maximum stock, reorder point and order quantity, companies can effectively determine the raw material inventory policy to avoid overstock or stockout. The study uses a 99% service level with a 1% risk of out-of-stock products. The results of the study obtained the safety stock value of silica sand 3,854 tons; gypsum 4,405 tons; trass 10,456 tons; and Fly Ash 511 tons. Then, the minimum inventory calculation is carried out, it is known that the minimum inventory results are in Fly ash raw material of 776 tons while the results for maximum inventory are in Trass of 34,613 tons. After the min-max calculation, the ordering policy for each material can be obtained, silica sand 5,255 tons, gypsum 9,111 tons, trass 22,534 tons, fly ash 776 tons.